2015
DOI: 10.1007/s00125-015-3596-6
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-based inhibition of IκB kinase/nuclear factor-κB pathway protects against diabetes-associated nephropathy and atherosclerosis in a mouse model of type 1 diabetes

Abstract: Aims/hypothesis The canonical nuclear factor-κB (NF-κB) pathway mediated by the inhibitor of NF-κB kinase (IKK) regulates the transcription of inflammatory genes involved in the pathogenesis of diabetes, from the early phase to progression and final complications. The NF-κB essential modulator binding domain (NBD) contained in IKKα/β is essential for IKK complex assembly. We therefore investigated the functional consequences of targeting the IKK-dependent NF-κB pathway in the progression of diabetes-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…65 Among the mechanisms activated by IL-17A in renal cells, the transcription factor NF-kB has special relevance in human and experimental DN. 9,40,[66][67][68][69] Numerous drugs used in clinical practice that have protective effects in DN also reduced the NF-kB activation. Moreover, direct inhibition of NF-kB activation by BAY 11-7082 reduced renal injury, inflammation, and hyperglycemia in experimental diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…65 Among the mechanisms activated by IL-17A in renal cells, the transcription factor NF-kB has special relevance in human and experimental DN. 9,40,[66][67][68][69] Numerous drugs used in clinical practice that have protective effects in DN also reduced the NF-kB activation. Moreover, direct inhibition of NF-kB activation by BAY 11-7082 reduced renal injury, inflammation, and hyperglycemia in experimental diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CNIs activated NF-κB in the entire vascular wall, including VSMC. This is relevant for CNI toxicity since NF-κB inhibition with parthenolide prevents experimental atherosclerosis and renal damage333536. Thus, synthetic or naturally occurring NF-κB small molecule inhibitors should be explored to prevent CNI-induced vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In normal conditions the IKKβ/NF-kB complex remains inactive in the hypothalamus, whereas in obese condition IKKβ/NF-kB gets activated and disrupts insulin/leptin signaling [75]. Recent report have shown that using SC-514 [76] and peptide-based inhibition [77] of IKK attenuated NF-κB activation with suppressed inflammation and reduced development of long-term diabetes inflammatory complications.…”
Section: Iκb Kinase (Ikk)mentioning
confidence: 99%